POLA PERMUKIMAN MEGALITIK DI SITUS KODEDEK, BONDOWOSO - Sulistyarto, Priyatno Hadi (BRIN, 2003)
Based on a study of megalithic settlements at the Kodedek site, Bondowoso, East Java, it is known that the existence of megalithic culture at the site is still strong. In addition, in this paper it can be seen how the application of settlement studies at the meso / semi-micro level or at the site level spatial unit. It is hoped that future studies in the same area can bring this area within the framework of a macro-level settlement study or at a regional level spatial unit. Given that in the Bondowoso area there are a large number of similar sites.